Public controversy and citizens' attitude formation about animal research: A case for scholarship and recommendations on conflicts at the science-society interface. - Elena Link; Katharina Emde-Lachmund; Sophie Bruns; Anja Dittrich; Meike Stiesch; Axel Haverich; Stefan Treue; Christoph Klimmt (PLoS ONE, 2024)
Activist groups attack animal research and put scientists and their institutions under pressure, whereas scientists often remain silent. We report an interdisciplinary research project driven by a communication science perspective on how citizens respond to news reports about animal research (3 experiments, overall N = 765) and a German science-initiated information platform ("Tierversuche verstehen"; controlled user study, N = 100). Findings demonstrate that a critical journalist perspective within neutral, two-sided news reports (e.g., skeptical expert statements or images of suffering animals) does not affect citizen opinion strongly. Information media provided by scientific institutions seem to be welcomed even by citizens who hold critical prior attitudes. From these results, we develop a set of recommendations for future public communication of animal research that builds on best practices in organizational and crisis communication. These suggestions are intended to empower animal researchers to actively participate in public debate to support citizens' informed attitude formation.